New species and host plants of Anastrepha (Diptera: Tephritidae) primarily from Peru and Bolivia - Norrbom, Allen L.; Rodriguez, Erick J.; Steck, Gary J.; Sutton, Bruce A.; Nolazco, Norma (Zootaxa, 2015)
Twenty-eight new species of Anastrepha are described and illustrated: A. acca (Bolivia, Peru), A. adami (Peru), A. amplidentata (Bolivia, Peru), A. annonae (Peru), A. breviapex (Peru), A. caballeroi (Peru), A. camba (Bolivia, Peru), A. cicra (Bolivia, Peru), A. disjuncta (Peru), A. durantae (Peru), A. echaratiensis (Peru), A. eminens (Peru), A. ericki (Peru), A. gonzalezi (Bolivia, Peru), A. guevarai (Peru), A. gusi (Peru), A. kimi (Colombia, Peru), A. korytkowskii (Bolivia, Peru), A. latilanceola (Bolivia, Peru), A. melanoptera (Peru), A. mollyae (Bolivia, Peru), A. perezi (Peru), A. psidivora (Peru), A. robynae (Peru), A. rondoniensis (Brazil, Peru), A. tunariensis (Bolivia, Peru), A. villosa (Bolivia), and A. zacharyi (Peru). The following host plant records are reported: A. amplidentata from Spondias mombin L. (Anacardiaceae); A. caballeroi from Quararibea malacocalyx A. Robyns & S. Nilsson (Malvaceae); A. annonae from Annona mucosa Jacq. and Annona sp. (Annonaceae); A. durantae from Duranta peruviana Moldenke (Verbenaceae); and A. psidivora from Psidium guajava L. (Myrtaceae).